2014
DOI: 10.1016/j.ajhg.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Early Austronesians: Into and Out Of Taiwan

Abstract: A Taiwan origin for the expansion of the Austronesian languages and their speakers is well supported by linguistic and archaeological evidence. However, human genetic evidence is more controversial. Until now, there had been no ancient skeletal evidence of a potential Austronesian-speaking ancestor prior to the Taiwan Neolithic ~6,000 years ago, and genetic studies have largely ignored the role of genetic diversity within Taiwan as well as the origins of Formosans. We address these issues via analysis of a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
142
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(156 citation statements)
references
References 54 publications
13
142
0
1
Order By: Relevance
“…These trees fit remarkably well with archaeological evidence that shows Austronesianspeaking cultures were some of the greatest ocean voyagers in human history, sailing from their homeland in Taiwan to settle on islands ranging in size from the 0.4-km 2 island of Anuta up to the 785,000-km 2 continental island of New Guinea (14,53,54). The archaeological, genetic, and linguistic evidence suggests that this expansion started ∼5,000 y ago and spread in a series of expansion pulses and pauses through Island South East Asia and the Pacific (52)(53)(54)(55). The cultures that evolved on these islands ranged from small kin-based groups, such as the Berawan (56), up to federated kingdoms, such as Southern Toraja (57).…”
Section: Big(ish) Data and Need For Computational Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…These trees fit remarkably well with archaeological evidence that shows Austronesianspeaking cultures were some of the greatest ocean voyagers in human history, sailing from their homeland in Taiwan to settle on islands ranging in size from the 0.4-km 2 island of Anuta up to the 785,000-km 2 continental island of New Guinea (14,53,54). The archaeological, genetic, and linguistic evidence suggests that this expansion started ∼5,000 y ago and spread in a series of expansion pulses and pauses through Island South East Asia and the Pacific (52)(53)(54)(55). The cultures that evolved on these islands ranged from small kin-based groups, such as the Berawan (56), up to federated kingdoms, such as Southern Toraja (57).…”
Section: Big(ish) Data and Need For Computational Methodssupporting
confidence: 52%
“…Previously published language-based phylogenies were used as a proxy for the population history of these cultures (52). These trees fit remarkably well with archaeological evidence that shows Austronesianspeaking cultures were some of the greatest ocean voyagers in human history, sailing from their homeland in Taiwan to settle on islands ranging in size from the 0.4-km 2 island of Anuta up to the 785,000-km 2 continental island of New Guinea (14,53,54). The archaeological, genetic, and linguistic evidence suggests that this expansion started ∼5,000 y ago and spread in a series of expansion pulses and pauses through Island South East Asia and the Pacific (52)(53)(54)(55).…”
Section: Big(ish) Data and Need For Computational Methodsmentioning
confidence: 57%
“…All variables used in this study were binary coded. Our coding criteria for political complexity and MHGs were based on variables in the Ethnographic Atlas and Standard Cross-Cultural Samples [22]. For political complexity, cultures were coded as low if they had no more than one level of jurisdictional hierarchy beyond the local community (acephalous societies and simple chiefdoms), or high if they had two or more levels of jurisdictional hierarchy beyond the local community (complex chiefdoms and states).…”
Section: Materials and Methods (A) Ethnographic Sources And Codingmentioning
confidence: 99%
“…For political complexity, cultures were coded as low if they had no more than one level of jurisdictional hierarchy beyond the local community (acephalous societies and simple chiefdoms), or high if they had two or more levels of jurisdictional hierarchy beyond the local community (complex chiefdoms and states). For a MHG to be coded as present in a culture there must be the concept of a god who (i) created or governs the cosmos, (ii) is active in human affairs and (iii) is specifically supportive of human morality [22]. For BSP to be coded as present in a culture there must be the concept of a supernatural agent or process that reliably monitors and punishes selfish actions, and this concept must (i) be widely advocated within the community, (ii) involve punishment of a broad range of selfish behaviours and (iii) apply to a wide range of community members (electronic supplementary material provides detailed coding criteria of all variables).…”
Section: Materials and Methods (A) Ethnographic Sources And Codingmentioning
confidence: 99%
“…Linguistic, archaeological, and genetic studies have demonstrated the complex nature of the process, where different components that helped to shape Lapita culture in Near Oceania each have their own unique history (1)(2)(3). Important evidence points to Taiwan as an Austronesian ancestral homeland with a more distant origin in South China (S China) (3,4,(9)(10)(11)(12), whereas alternative models suggest S China to North Vietnam (N Vietnam) (7) or a Southeast Asian (SE Asian) origin based mainly on human genetic data (5). The complexity of the subject is further manifested by models theorizing how different spheres of interaction with Near Oceanic indigenous populations during Austronesian migrations have contributed to the origin of Lapita culture (1)(2)(3), ranging from the "Express Train" model, assuming fast migrations from S China/Taiwan to Polynesia with limited interaction (4), to the models of "Slow Boat" (5) or "Voyaging Corridor Triple I," in which "Intrusion" of slower Austronesian migrations plus the "Integration" with indigenous Near Oceanic cultures had resulted in the "Innovation" of the Lapita cultural complex (2,13).…”
mentioning
confidence: 99%